Anoftalmia clínica bilateral associada à hidrocefalia congênita em cão - Palumbo, Mariana Isa Poci [UNESP]; Conti, Jorge Piovesan [UNESP]; Doiche, Danuta Pulz [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Lourenço, Maria Lúcia Gomes [UNESP]; Machado, Luiz Henrique de Araújo [UNESP] (My University, 2011)
The complete absence of the eyeball is rare in dogs and cats, and hydrocephalus is commonly seen as a congenital disorder in toy or brachycephalic dogs before one year old. This paper describes for the first time in Brazil the occurrence of bilateral clinical anophthalmia associated to congenital hydrocephalus in a dog.
Bilateral clinical anophthalmia associated with congenital hydrocephalus in the dog
Keywords: Congenital disorders; Dog; Neurology; Ophthalmology